From One of the Earliest Greek Lectionaries to a Coptic Gospel Codex: Reassessing Lectionary 1043 (P. Vindob. G 2324). - Suciu, Alin (Novum Testamentum, 2026)
This study reassesses the five Greek gospel leaves preserved in Vienna as P. Vindob. G 2324 (Gregory-Aland Lectionary 1043), long regarded as one of the earliest extant lectionaries. Through codicological and paleographic analysis, this article argues that the fragments in question did not originate as an independent lectionary, but rather formed part of the Sahidic Gospel codex sa 131 from the White Monastery in Upper Egypt. The scribe who copied the Coptic text also added selected Greek gospel passages at the end of the manuscript. The same scribal hand can further be identified in a companion Sahidic codex of Acts and Catholic Epistles. The codicological reconstruction of the original manuscript sheds new light on the relationship between Greek and Coptic in seventh-century Christian Egypt.